Medialnost literature - Schanze, Helmut (Slavistična revija, 2017)
Media studies have a reputation as a new and innovative field, but "mediality" has been a research topic since the 1970s. It appears that what has been uniquely German is the question of literary history as media history, which was first treated in the context of Germanic and Romance studies. In the Anglo-American world media have been treated in the context of film and television. In this article I will return to the epistemological bases of media studies via questions about the "mediality of literature". There are three different points of view.
Keywords: Benjamin, Walter, 1892-1940; Kittler Friederich, 1943-; književnost; literature; mass media; medialnost; množični mediji; Rusch, Gebhardt; zaslonski mediji